Interview with Dr. Prakash Sharan Mahat Honorable Minister, Ministry of Energy, Government of Nepal - Pokharel, Govind Raj (Hydro Nepal: Journal of Water, Energy and Environment, 2010)
Not Avaiable. DOI: 10.3126/hn.v5i0.2491 Hydro Nepal Vol. 5, July 2009 Page:52-53